so, substitute one Y value in the other equation
3x - 10 = 2x - 5
3x -2x - 10 = 2x - 2x - 5
x - 10 = -5
x -10 +10 = -5 + 10
x = 5
Then, Y = 3(5) - 10 = 5
2006-11-13 13:24:27
·
answer #1
·
answered by just browsin 6
·
0⤊
0⤋
1. Set formulas equal to each other
3x-10=2x-5
2. Move over the 2x, and subtract
x-10=-5
3. Add 10 to both sides
x-10+10=-5+10
4. Solve for x
x=5
5. Plug x(5) in to any formula
Y=2(5)-5
6. Solve
Y=10-5
Y=5
2006-11-13 21:29:33
·
answer #2
·
answered by luke 2
·
0⤊
0⤋
Y=3x-10
Y=2x-5
set Ys equal
3x-10=2x-5
x=5
2006-11-13 21:23:46
·
answer #3
·
answered by jesuisbete 2
·
0⤊
0⤋
Y= 3x - 10
Y= 2x - 5
since we have both in terms of y, it is easiest to use y=y so
3x-10=2x-5 subtract 2x from each side
x-10=-5 add 10 to each side
x=5
now substitute
y=2*5-5=10-5=5
check
5*3*5-10=15-10=5
2006-11-13 21:28:53
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
y=y so then since y=3x-10 and y=2x-5 then 3x-10=2x-5, which you can reduce to x=5 and u plug that into one of the original problems so its like y=2(5)-5 and then y=5
2006-11-13 21:30:57
·
answer #5
·
answered by gamepro1990 2
·
0⤊
0⤋
If you are solving for x, then you can set the two equations equal to each other:
3x - 10 = 2x - 5
Now add ten to each side:
3x = 2x + 5
Now subtract 2x from each side:
x = 5
Now plug in x = 5 into one of the original equations.
y = 3(5) - 10
y = 15 - 10
y = 5
2006-11-13 21:26:04
·
answer #6
·
answered by kendall_krazy49 2
·
0⤊
0⤋
y = 3x - 10
y = 2x - 5
intent is to "eliminate" x or y, so as to have an equation in
one variable, x or y, that can therefore be solved.
in this example, if we subtract equation 2 from equation 1,
0 = x -5
so x = 5
if x is 5, the equation y = 3x-10 says that y = 5
if x is 5, the equation y = 2x-5 also says that y = 5
solution is x=5, y = 5
2006-11-13 21:47:29
·
answer #7
·
answered by paladin 1
·
0⤊
0⤋
since both equal y, u can equate them:
3x - 10 = 2x - 5
3x - 2x =10-5
x = 5
Sub x = 15 into either of the original equations to get y.
2006-11-13 21:25:27
·
answer #8
·
answered by Clawd 1
·
0⤊
0⤋
y=3x-10 & y=2x-5
3x-10=2x-5
3x-2x=10-5
x=5
y=3*5-10
y=5
2006-11-13 21:25:19
·
answer #9
·
answered by 6
·
0⤊
0⤋
1. Pick either equation and solve for x.
2. Once you find what x equals, plug it into the other formula you did not use.
Then, you should be able to figure out what the answer is.
2006-11-13 21:25:13
·
answer #10
·
answered by Ryan T 2
·
0⤊
0⤋